OWNERSHIP STRUCTURE, FREE CASH FLOW, ASSET STRUCTURE AND DIVIDEND POLICY ON DEBT POLICY - Tahir, Nirina; Hormati, Asrudin; Zainuddin, Zainuddin (Universitas Sam Ratulangi, 2020)
This study is designed based on problems related to debt policy. The debt policy in every company has a direct effect on the financial position. The use of debt that which too high provides great risk, but if the companies are able to manage debt properly; then the use of debt shall increase profits for shareholders. The purpose of this study was to determine and analyze the effects of managerial ownership, institutional ownership, free cash flow, assets structure, and dividend policy on companies indexed LQ-45 wich listed on the Indonesia Stock Exchange. The sampling technique of this study is purposive sampling which produced 85 observations. This study uses secondary data in the form of annual reports. The tool of analysis of this study is multiple regression with support of statistical package for social scientists (SPSS) software. The results show that: (1) managerial ownership has no effect on debt policy; (2) institutional ownership has a negative effect on debt policy; (3) free cash flow has a negative effect on debt policy; (4) assets structure has a negative effect on debt policy and (5) dividend policy has no effect on debt policy.